Political Instability and the Informal Economy. (September 2016) - Elbahnasawy, Nasr G.; Ellis, Michael A.; Adom, Assandé Désiré
Highlights: We investigate the political environment that allows the informal economy to develop. Political instability, social polarization, and an autocratic authority pattern increase informality. Efforts to reduce informality should focus on political reforms. Democratic reforms can increase informality if it increases political instability. Summary: Understanding the determinants of the informal economy is a crucial issue in economic development because of its effect on economic performance as well as undermining the construction of indicators to monitor economic development. While the focus on the literature has been on the proximate causes of informal production, such as taxation, we investigate the political environment that causes governments to choose policies that allow the informal economy to develop. We argue that the political environment affects the government's incentive to invest in the efficiency of tax collection, and therefore the ability of the government to detect informal production. We show that political instability, social polarization along ethnic and religious lines, and an autocratic authority pattern are associated with a larger informal economy. The results suggest that efforts to reduce informal production should shift from an emphasis on the proximate causes to political reforms. Since polarization along ethnic and religious lines is structural, reforms should focus on reducing political instability and autocracy. However, the results imply that democratic reforms that change the authority pattern from autocracy to democracy can increase informal economic activity if it increases political instability.